Quantitative Determination of 15 Active Components in Lepidium meyenii with UHPLC-PDA and GC-MS. (1st September 2021) - Xu, Yao-qing; Qiao, San-yang; Wang, Zi-qian; Cui, Meng-yao; Tan, Dao-peng; Feng, Hong; Mei, Xing-sha; Li, Geng; Cheng, Long
Abstract : In this study, a method using ultrahigh-performance liquid chromatography with photodiode array (UHPLC-PDA) was established and validated for the simultaneous quantification of 10 active components, including eight macamides and two glucosinolates, in Lepidium meyenii (maca). A gas chromatographic mass spectroscopy (GC-MS) method was used to determine the levels of three benzyl isothiocyanates and two sterols in maca. Liquid chromatographic separation was achieved on a Waters Acquity UHPLC HSS T3 column (2.1 mm × 100 mm, 1.8 μ m) with gradient elution over 15 min. The mobile phase was (B) acetonitrile-(A) 10 mM aqueous ammonium phosphate, and the detection wavelength was 210 nm. The gas chromatographic separation was performed on an SH-Rxi-1 MS column, and the ionization mode was electron ionization (EI). Two methods were confirmed to have desirable precision (RSD < 1.58%), repeatability (RSD < 1.97%), stability (RSD < 1.76%), and good linearity ( R 2 ≥ 0.999) within the test range. The recoveries were in the range of 96.79–109.99%, with an RSD below 2.39%. We applied the established methods and successfully analyzed 15 compounds in maca processed under different drying conditions, providing a comprehensive reference for maca processing method of development. In summary, this study provided two rapid and effective methods for the quantification of 15 active components, which contributed to the in-depth maca quality control and provided a reference for the development of maca products.